Low input capture Hi-C (liCHi-C) identifies promoter-enhancer interactions at high-resolution - Laureano Tomás-Daza; Llorenç Rovirosa; Paula López-Martí; Andrea Nieto-Aliseda; François Serra; Ainoa Planas-Riverola; Oscar Molina; Rebecca McDonald; Cedric Ghevaert; Esther Cuatrecasas; Dolors Costa; Mireia Camós; et al. (Nature Communications, 2023)
Here the authors present the low input capture Hi-C (liCHi-C) method, a cost-effective, flexible method to map and robustly compare promoter interactomes at high resolution. liCHi-C identifies new disease-associated genes and structural variants to ultimately illuminate their pathogenic effects.